2017
DOI: 10.18632/aging.101279
|View full text |Cite
|
Sign up to set email alerts
|

Aging effects on intestinal homeostasis associated with expansion and dysfunction of intestinal epithelial stem cells

Abstract: Intestinal epithelial stem cells (IESCs) are critical to maintain intestinal epithelial function and homeostasis. We tested the hypothesis that aging promotes IESC dysfunction using old (18-22 months) and young (2-4 month) Sox9-EGFP IESC reporter mice. Different levels of Sox9-EGFP permit analyses of active IESC (Sox9-EGFPLow), activatable reserve IESC and enteroendocrine cells (Sox9-EGFPHigh), Sox9-EGFPSublow progenitors, and Sox9-EGFPNegative differentiated lineages. Crypt-villus morphology, cellular composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 69 publications
7
51
0
Order By: Relevance
“…Other studies have reported sometimes similar, sometimes conflicting phenotypes of aging ISCs: Moorefield et al (179) report increased villus height and Paneth cells in 18-to 22-monthold mice, increased ISC proliferation, and expansion of the ISC population (identified in this study by moderate expression of Sox9), while also demonstrating that crypt organoid cultures from old mice yield fewer and less-complex organoids. The authors also find increased apoptosis Aging of the stem cell compartment of the small intestine of mice.…”
Section: Aging In the Mammalian Intestinesupporting
confidence: 68%
“…Other studies have reported sometimes similar, sometimes conflicting phenotypes of aging ISCs: Moorefield et al (179) report increased villus height and Paneth cells in 18-to 22-monthold mice, increased ISC proliferation, and expansion of the ISC population (identified in this study by moderate expression of Sox9), while also demonstrating that crypt organoid cultures from old mice yield fewer and less-complex organoids. The authors also find increased apoptosis Aging of the stem cell compartment of the small intestine of mice.…”
Section: Aging In the Mammalian Intestinesupporting
confidence: 68%
“…Indeed, our study showed that older animals displayed worse colonic inflammation and injury microscopically prior to stroke induction when compared to younger counterparts, indicating innate biological differences with age. Consistent with these findings, a recent study demonstrated that older mice showed increased apoptotic cells in intestinal crypts and villi, with functional impairment of isolated intestinal epithelial stem cells, suggesting a reduced capacity for tissue repair following injury (Moorefield et al, ).…”
Section: Discussionmentioning
confidence: 60%
“…[ 166,167 ] Accumulating evidence suggests the aged intestinal epithelium—instead of being hypo‐proliferative as suggested by instinct—contains more proliferating cells and has a higher proliferation rate. [ 168–171 ] Concomitantly, there is also an increase in apoptosis in the stem cell population, [ 170,171 ] and a retarded response to fasting or irradiation‐induced damage. [ 168,172,173 ] This increase in proliferation may be a strategy to combat aging‐associated increase in stem cell death.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Nevertheless, hyper‐proliferation may increase the risk of genetic abnormality and cancer development. Moreover, several studies report an increase in villi height, [ 171,173 ] possibly in attempt to expand the absorptive surface area of the gut to compensate the reduced absorptive capacity during aging.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%